The Effects of Mindfulness Training and Dialectical Behavior Therapy on Drug Craving and Emotion Self-regulation in Clients With Substance-dependence - Mojtaba Moghadam; Behnam Makvandi; Farah Naderi (Iran University of Medical Sciences, 2021)
Background: Drug craving is a strong and resistant yearn to consume drugs; if not met, his condition would be followed by biopsychological issues, such as fatigue, anxiety, aggression, and depression. This study determined the effects of mindfulness training and Dialectical Behavior Therapy (DBT) on drug craving and emotion regulation in clients with substance dependence. Methods: This was a quasi-experimental study with a pre-test, post-test and a control group design. The research population included all the clients with drug use disorders, referring to midterm substance-dependence treatment centers in Baghmalek City, Iran, in 2018. Using a convenience sampling method, 60 clients with drug use disorders, willing to participate in the project were selected. Accordingly, they were randomly assigned into two experimental groups (mindfulness training & dialectical behavior therapy), and a control group (n=20/group). The research instruments included the Substance Craving Questionnaire-NOW (SCQ-NOW) and the Emotion Regulation Questionnaire (ERQ). The first experimental group underwent twelve 45-minute weekly sessions of mindfulness training. Besides, the second experimental group received twelve 45-minute weekly sessions of dialectical behavior therapy. The control group received no treatment. Multivariate Analysis of Covariance (MANCOVA) was applied in SPSS to analyze the obtained data. Results: The Mean±SD post-test scores of drug craving for mindfulness training, dialectical behavior therapy, and control groups were 130.02±8.01, 124.75±7.58, and 212.19±12.32, respectively. The collected results suggested that the provided intervention programs effectively reduced drug craving and improved emotion regulation in the examined clients (P=0.0001). Additionally, there was no significant difference between the effects of mindfulness training and dialectical behavior therapy on drug craving and emotion regulation.  Conclusion: In addition to decreasing drug craving, mindfulness training and dialectical behavior therapy can improve emotion regulation in subjects with drug use disorders.